Um estudo sobre o uso de duas flautas doces tocadas simultaneamente por um só flautista na música contemporânea - Lissandra Sampaio Ribeiro (2024)
This work aims to carry out a study on the use of two recorders played simultaneously by a single flutist, with the objective of reflecting on the challenges the musician faces when performing repertoire for this modality of instrumentation. For this purpose, three works from the contemporary music repertoire are addressed: Ende, by Louis Andriessen; Diaulos, by Bruno Giner; and Onírica - Paisagem Noturna, by Hudson Lacerda and Lissandra Sampaio Ribeiro. In the first chapter, focusing on Ende, and in the second chapter, on Diaulos, technical, interpretative, and linguistic aspects were raised and analyzed, based on the study and performance of these pieces. The third chapter reports on the creation of the piece Onírica – Paisagem Noturna, carried out in a collaborative interpreter-composer process.